Open Data Drivers and Barriers within Public Organisations - Vrbek, Sanja; Keržič, Damijana; Jukić, Tina (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Open Government Data (OGD) is a public good whose impact extends beyond the public sector, contributing to economic development and societal well-being. However, data alone do not create value, as the mere publication of data does not guarantee automatic positive effects in practice. Public organisations play a key role in this process by ensuring the provision of high-quality, accessible, and timely data and actively engaging within the broader ecosystem of data users. Although Slovenia has a favourable legislative and institutional framework for OGD, significant challenges persist at the organisational level. To better understand these challenges and identify strategies for overcoming them, this paper analyses scientific articles (from the WoS and Scopus databases) and examines the drivers and barriers within public organisations that influence the opening of data. A systematic review of these "universal" factors provides a foundation for addressing Slovenia's specific challenges and advancing the successful implementation of OGD initiatives.